Socio-Economic Conditions and Adoption of Regional Tax Information System Innovations (At the Cimahi City Government Regional Revenue Management Agency) - Eko Setyanto; Rini Handayani (Jurnal Manajemen Indonesia, 2020)
In the aim of increasing accountability and receipt of local revenue, especially Regional Taxes, Cimahi City Regional Government, namely the Regional Revenue Agency Management Agency (Bappenda) of Cimahi City, made an innovation in the form of regional tax information systems including e-pad and so on. local tax information system, especially by employees of Cimahi City Bappenda. Bappenda of Cimahi City, in particular has made various efforts such as improving the socio-economic conditions of its employees such as education, income, age, and cosmopolitan. This study aims to determine the socio-economic conditions and the adoption of innovative local tax information systems in Cimahi City Bappenda. This research was conducted using quantitative methods. Data was obtained using a questionnaire distributed to employees of Cimahi City Bappenda. The analysis of this study uses multiple linear regression to determine the effect of education, income, age and cosmopolitan on the adoption of local tax information system innovations either simultaneously or partially. The results showed that education, income, age and cosmopolitan influenced the adoption of regional tax information system innovations in a positive and significant part, and the relationship of all independent variables simultaneously with the adoption of local tax information system innovations included in the criteria of a very strong relationship. Keywords— Innovation Adoption; Socio-Economic; Regional Tax Information System.